Genome-wide association analysis of Monilinia fructicola lesion in a collection of Spanish peach landraces - Martínez-García, Pedro J.; Mas-Gómez, Jorge; Prudencio, Ángela S.; Barriuso, Juan José; Cantín, Celia M. (Frontiers in Plant Science, 2023)
Brown rot, caused by the Monilinia spp., is the disease that causes the greatest losses in stone fruit worldwide. Currently, M. fructicola has become the dominant species in the main peach production area in Spain. The fruit cuticle is the first barrier of protection against external aggressions, and may have a key role in the susceptibility to brown rot. However, information on the role of skin fruit on the resistance to brown rot in peach is scarce. Previous genetic analysis in peach have demonstrated that brown rot resistance is a complex and quantitative trait in which different fruit parts and resistance mechanisms are involved. To search for genomic areas involved in the control of the cultivar susceptibility to brown rot and to elucidate the role of fruit skin against this infection, we have studied, for two consecutive seasons (2019 and 2020), the fruit susceptibility to M. fructicola, together with fruit cuticle thickness (CT) and density (CD), in a collection of 80 Spanish and 5 foreign peach cultivars from the National Peach Collection at CITA (Zaragoza, Spain). Brown rot incidence, lesion diameter and severity index were calculated after 5 days of inoculation on non-wounded fruit. The peach collection has also been genotyped using the new peach SNP chip (9+9K). Genotypic and phenotypic data have been used to perform a Genome-Wide Association Analysis (GWAS). Phenotyping has shown a wide variability on the brown rot susceptibility within the Spanish germplasm as well as on CD and CT. The GWAS results have identified several significant SNPs associated with Disease severity index (DSI), CD and CT, five of which were considered as reliable SNP-trait associations. A wide protein network analysis, using 127 genes within the regions of the reliable SNPs and previously identified candidate genes (169) associated with Monilinia spp. resistance, highlighted several genes involved in classical hypersensitive response (HR), genes related to waxes layers as ceramidases and lignin precursors catalysers and a possible role of autophagy during brown rot infection. This work adds relevant information on the complexity resistance mechanisms to brown rot infection in peach fruits and the genetics behind them.